Middle Class Evolving To Precariat: Labour Conditions for the 21st Century - Andoni Alonso; Sílvia Ferreira; David Alonso (Social Work & Society, 2016)
Middle Class has become a confusing term. Low, medium and high middle classes are attempts to reorganize meaning. The appearance of new middle classes in emergent countries adds new difficulties to make sense of the concept. This is the reason why some authors disqualify the very notion of middle class. This paper tries to articulate the appearance of a new social class, the precariat that absorbs part of the falling members of middle class and working class in general. It is proposed also to revise two basic concepts concerning middle classes: the public good and consumerism in order to give political content for this concept. Public should be transformed into commons and de-growth should be a guideline for future political action. -- La clase media se ha convertido en un término confuso.  Las clases bajas, medias y altas dentro de la clase media, constituyen el intento de reorganizar su significado. La aparición de nuevas clases medias en los países emergentes añade nuevas dificultades a la hora de dotar de sentido a este concepto.  Esta es la razón por la cual algunos autores descalifican la noción misma de clase media. Este artículo trata de articular la aparición de una nueva clase social caracterizada por la precariedad que absorbe a parte de los miembros que han caído de la clase media y la clase trabajadora en general.  Se propone igualmente revisar dos conceptos básicos relativos a la clase media: el bien público y el consumo; a fin de dotar de contenido político a este concepto. Lo público debe transformarse en bien común y el nivel de de-crecimiento debería ser una guía para el futuro de la acción política.